Real-world outcomes of concomitant antidepressant and statin use in primary care patients with depression: a population-based cohort study - De Giorgi, R; De Crescenzo, F; Cowen, PJ; Harmer, CJ; Cipriani, A (BioMed Central, 2023)
Background Antidepressants are licensed for use in depressive disorders, but non-response and poor adherence to treatment affect a considerable number of patients. Pre-clinical and clinical evidence suggest that statins can augment the effects of antidepressants. However, the acceptability and tolerability of combining statins with antidepressants are unclear, and their add-on efficacy has only been shown in small, short-term clinical trials. Observational data can provide complementary information about treatment effects on larger samples over longer follow-ups. In this study, we therefore assessed the real-world acceptability, tolerability, and efficacy of concomitant antidepressant and statin treatment in depression.